Determinants of creative thinking: the effect of task characteristics in solving remote associate test problems. (3rd April 2022) - Sio, Ut Na; Kotovsky, Kenneth; Cagan, Jonathan
Abstract: Creative problem solving is often conceptualised as a process of search. However, little is known about the difficulties of carrying out this search process. We conducted three studies examining how strongly different task characteristics impact creative problem-solving performance. In Study 1, regression analyses on normative data of Remote Associates Test (RAT) problems identified key task characteristics that best predict performance. We replicated these findings in a sample that was more diverse with respect to age and education background and proposed that two key factors may interact in predicting RAT problem difficulty (Study 2). We then confirmed this prediction in a pre-registered study (Study 3). Our results suggest that (a) the semantic distance between the cues and the answer and (b) the number of strong but irrelevant associates are important determinants of RAT problem difficulty, and that their influence is interdependent. Implications for theories and for studies aimed at improving creative problem-solving performance are discussed.